Automatic Corporation Water Supply Control Using Arduino - Bharathidasan, S.; Y. Farisha; R. Harisoothanakumar; U. Rajeshwari; J. Suryaprabha (Asian Journal of Electrical Sciences, 2019)
The main aim of our project is to control the corporation water supplying for several areas from one control board. Here we have used Arduino board for controlling the System. For the communication purpose Radio Frequency (RF) transmitter and receivers are used. This will made the system more efficient for signal and information passing. Our project proposes an economic, efficient, eco-friendly system for controlling the corporation water supply. The advantages by our project are time management, proper drinking water supply with defined time, can reduce wastage of water.